2013
DOI: 10.2174/0929867311320060008
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of HOX B13 Expression in Urinary Bladder Cancer Progression

Abstract: Urinary bladder cancer is a common malignancy in industrialized countries. More than 90% of bladder cancer originates in the transitional cells. Bladder transitional cancer prognosis is, according to the most recent definition related to the level of tumor infiltration, characterized by two main phenotypes, Non Muscle Invasive Bladder Transitional Cancer (NMIBC) and Muscle Invasive Bladder Transitional Cancer (MIBC). The genetic profile and the clinical course of the two subtypes are completely different, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…22 Recent reports have indicated that the certain HOX genes was dysregulated in a variety of malignancies such as acute myeloid leukemia, as well as breast, prostate, bladder, lung, and thyroid cancers. [23][24][25][26][27][28] In our study, we found that HOXA3 was upregulated in colon cancer tissues compared with adjacent non-tumorous tissues, suggesting the abnormal expression of HOXA3 might be related with colon cancer. Besides, we found that high stage cancers possessed high HOXA3 level, and patients with high HOXA3 levels possessed low survival rate.…”
Section: Discussionmentioning
confidence: 51%
“…22 Recent reports have indicated that the certain HOX genes was dysregulated in a variety of malignancies such as acute myeloid leukemia, as well as breast, prostate, bladder, lung, and thyroid cancers. [23][24][25][26][27][28] In our study, we found that HOXA3 was upregulated in colon cancer tissues compared with adjacent non-tumorous tissues, suggesting the abnormal expression of HOXA3 might be related with colon cancer. Besides, we found that high stage cancers possessed high HOXA3 level, and patients with high HOXA3 levels possessed low survival rate.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, physical exercise is (a) an effective tool for enhancing cognitive performance and regulating mood and (b) produced morphological and functional changes of brain regions that play central roles in successful everyday functioning, such as frontal and temporal cortices, and the hippocampus located in the inner (medial) region of the temporal lobe. The frontal lobe is important for cognitive function (Iavarone et al, 2007; Chieffi et al, 2009, 2012; Boscia et al, 2015), the temporal lobe for memory function (Chieffi et al, 2004, 2014a, 2015; Marra et al, 2013; Franco et al, 2014). The factors most likely involved in exercise-induced hippocampal neurogenesis are the microcirculation and the production of neurotrophic factors such as the BDNF, VEGF, and IGF-1 (Cotman et al, 2007).…”
Section: Links With Brainmentioning
confidence: 99%
“…Both HOXA13 and HOXB13 are gene members of HOX family. Their role in cancer has been widely studied[9092] and these genes were implicated in bladder cancer progression[93, 94] and poor prognosis[95]. The different expression of HOXA13, HOXB13 and OTX1 genes between TCCSUPPi and TCCSUP as well as HOXB 13 gene between EJ28Pi and EJ28 suggest that regulatory mechanism of these genes varied between these cell lines.…”
Section: Discussionmentioning
confidence: 99%